Exploring a path of vegetation restoration best suited for a photovoltaic plant in the Hobq desert - Cai, Jiale; Meng, Zhongju; Meng, Ruibing; Li, Haonian; Chen, Xiaoyan; Ren, Xiaomeng; Guo, Lijun; Hao, Meijun (Frontiers in Environmental Science, 2024)
To investigate the soil improvement effects of different vegetation restoration measures during the operation and maintenance of photovoltaic power plants in the Hobq Desert. This study determined the soil grain size composition and soil nutrient content of 0-5 cm under four vegetation restoration measures and within the mechanical sand barriers by laser diffraction techniques and chemical experiments.The results showed that: (1) Soil particle size composition in the study area is predominantly sandy, with 1.02%, 6.63%, 5.34% and 2.61% less sand in Leymus chinensis (YC), Glycyrrhiza uralensis (GC), Artemisia ordosica Krasch (YH) and Hedysarum scoparium (HB), respectively, compared to mechanical sand barriers(CK).Soil particle distributions of YC, GC, and HB showed better sorting and more concentrated patterns, and all four vegetation restoration measures had higher fractal dimensions than CK. ( 2) AN (Alkali-hydrolyzable Nitrogen) content performance:The content of YC, GC, and HB was significantly higher than that of YH and CK, AP (Available Phosphorus) content did not differ significantly between measures, AK (Available Potassium) content was higher than that of CK in all measures, with YC content being the highest and SOM content being the highest for GC. (3) Soil total nutrient is unstable across vegetation restoration measures. Overall, the performance showed that the three vegetation restoration measures, YC, GC, and HB, were more evident in the soil total nutrient content improvement. Each particle size characteristic parameter and soil nutrient response vegetation restoration measures ameliorate sandy soil in PV power plants during operation and maintenance. YC and GC have the most apparent effect on soil amelioration.